(untitled) (diségno, 2020)
Urban maps represent the simplified drawing of a complex world (urban space) where material and immaterial phenomena, problems and solutions coexist; they are a tool used by individuals to perceive and act in space. In our current socio-urban context these representations are particularly interesting, above all due to the complexity of contemporary metropolises. Maps accompany us in our complex “urban” life more as maps of complexity than maps of the city. The contribution tackles this issue from the point of view of representation and the individual. It illustrates an interdisciplinary study that analyses the complexity of represented space, i.e., of the urban (such as spatial and social concentration, anthropological expression and system) and the problems linked to the complexity of its representation (i.e., the complexity of urban maps) which is solved by simplexity. It also analyses man’s capacity to act and move in real space (linked to the vital impulses of the organism, propriocetion and kinesthesia and the wonderful and extremely plastic ability to move in the environment) and thus the possibility of an individual to act and move in space through representation – linking his action to represented space and exploiting his brain’s ability to foresee movement in the drawing, i.e., in the map.